2022
DOI: 10.1186/s13104-022-05932-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic problems require systemic solutions: the need for coordination and cooperation to improve research quality

Abstract: Various factors contribute to low reproducibility and replicability of scientific findings. Whilst not all of these are necessarily problematic, there is growing acceptance that there is room for improvement. Many sectoral organisations have a role to play in this, by refining incentives and rewards, promoting specific behaviours such as open research practices, and exploring innovations in grant funding and scientific publishing. However, given the systems nature of the challenge, real change will require the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The first three explanations do not provide a good excuse, they are rather indicative of careless or egoistic behaviour -scientific communities can justifiably take action against them: No. 1 does not work, since there is so little agreement on the ordinary level of reproducibility that we cannot just take its understanding for granted; researchers may be unaware of this, but institutions, organizations, projects, and bottom-up initiatives are already raising that awareness [18] and will need to continue to do so. No.…”
Section: Reproducibility Claimsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first three explanations do not provide a good excuse, they are rather indicative of careless or egoistic behaviour -scientific communities can justifiably take action against them: No. 1 does not work, since there is so little agreement on the ordinary level of reproducibility that we cannot just take its understanding for granted; researchers may be unaware of this, but institutions, organizations, projects, and bottom-up initiatives are already raising that awareness [18] and will need to continue to do so. No.…”
Section: Reproducibility Claimsmentioning
confidence: 99%
“…Reproducibility is known to be one of the major challenges to open science and the scientific process at large [16]; e.g., examining applied mathematics papers, Riedel et al [17] find the reported results to be completely reproducible in only four out of 108 cases, and partially reproducible in only one other case. To advance on this challenge, reproducibility networks are being formed, for which the RIOT principles (reproducibility, interpretability, openness, transparency [18]) were formulated as guidelines, complementing the FAIR principles. Unfortunately, when working toward an improved reproducibility and compliance with the FAIR principles, communities risk overshooting by formulating excessive demands on the data provenance (i.e., origin and genesis) documentation.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst not all of these factors are necessarily problematic, we believe there is “room” for improvement and development in this research field. For this reason, we propose some state-of-the-art approaches to minimizing the frequency of commonly observed limitations, based on potential solutions that are observed to be universal in empirical research (Lin et al, 2011 ; Boutron and Ravaud, 2018 ; Brown et al, 2018 ; Jaschke et al, 2018 ; Sala and Gobet, 2020 ; Gustavson et al, 2021 ; Ganley et al, 2022 ), and likewise can be applied to this specific domain, too.…”
Section: Discussing the Ways Forwardmentioning
confidence: 99%
“…In another way, proper funding and personnel for more pilot and feasibility studies should be important, minimizing many small, non-randomized studies with cross-sectional survey data, and a variety of non-validated questionnaires (Brown et al, 2018 ). Also, partnerships across researchers in academia and research organizations outside of academia (e.g., music industries) or private companies should result in the reassurance of data integrity and results in quality generated in this domain (Ganley et al, 2022 ).…”
Section: Discussing the Ways Forwardmentioning
confidence: 99%
“…The remedies for low reproducibility is thought to be enhanced scientific rigor, meaning that, for example, statistical methods should be strengthened, the analysis plan should be prepublished, collaboration across labs should be stimulated, data should be made openly available, and detailed experimental procedures should be reported ( Munafo et al, 2017 ; Stevens, 2017 ; Ganley et al, 2022 ; Lu and Daugherty, 2022 ).…”
Section: Introductionmentioning
confidence: 99%